Genetic characterization of rainfed upland New Rice for Africa (NERICA) varieties - Fukuta, Y.; Konisho, K.; Senoo-Namai, S.; Yanagihara, S.; Tsunematsu, H.; Fukuo, A.; Kumashiro, T. (Japanese Society of Breeding, 2012)
A total of 18 rainfed upland New Rice for Africa (NERICA) varieties were categorized as the heavy panicle and low tillering types and early heading, in compared with 32 different varieties. These chromosome components were clarified using 243 SSR markers which showed polymorphism among NERICA varieties and their parents, CG 14 (O. glaberrima Steud.) and one of the recurrent parents, WAB-56-104 (O. sativa L.). NERICA varieties were classified into three groups, which corresponded with these parents' continuation including two exceptions, NERICAs 14 and 17, by a cluster analysis using polymorphism data of SSR markers and 14 differential markers among them were selected to classify NERICA varieties. However, three groups: NERICAs, 3 and 4, NERICAs, 8, 9 and 11 and NERICAs, 15 and 16 were not distinguishable. Association analysis was carried out for characterization of NERICA varieties by using SSR markers genotype and phenotype of agronomic traits. A total of 131 quantitative trait loci between SSR markers and 11 agronomic traits were detected. The characteristics of early maturity and heavy panicle of upland NERICA varieties were succeeded from Asian rice varieties and the characteristics of high dry matter production and late heading were introduced from CG 14 and the other varieties.